(untitled) (Medical Forum Monthly, 2023)
Objective: To assess if hyponatremia is associated with pregabalin. Pregabalin, an analog of the neurotransmitter γ-aminobutyric acid, possesses analgesic, anticonvulsant, and anxiolytic properties. Study Design: A prospective randomized interventional trial study Place and Duration of Study: This study was conducted at the Jinnah Hospital dialysis center from 01st January 2021 to 31st December 2021. Materials and Methods: All the patients with hyponatremia & taking pregabalin were included in the study. Although hyponatremia (when serum sodium level below 135 mmol/L) is the most common abnormality of electrolytes observed in hospitalized patients, it is typically associated with certain drugs such as diuretics, antidepressants, and antiepileptic medications. Notably, hyponatremia as a side effect of pregabalin has not been reported due to its relatively recent introduction. However, we present a few clinical scenarios where it is highly probable that hyponatremia was associated with pregabalin. Results: Out of 60 patients with hyponatremia, ten were found to be taking pregabalin. Three out of 10 (30%) cases of hyponatremia were found to be associated with pregabalin. These case scenarios are discussed in detail in the main body of this study. Conclusion: While hyponatremia is an infrequent occurrence, it is a potential side effect of pregabalin. Therefore, caution should be exercised when prescribing pregabalin to patients who are at a higher risk of developing hyponatremia